Women Behaving Badly: Problematisation and Biopolitical Governance of Gender in the New Zealand Abortion Debate: (SAANZ postgraduate essay prize winner 2021) - Lawley, Amelia (New Zealand Sociology, 2022)
Abortion in New Zealand is at a critical juncture as the current government pursues its decriminalisation. Since colonisation, access to abortion has been regulated in myriad ways, from capital punishment and hard labour to the tacit collusion between women and doctors represented by the mental health exception enshrined in legislation in the 1970s. This article employs the Foucauldian concept of problematisation to identify how women and abortion have been framed in key historical texts, such as laws and government inquiries and the rhetoric of the anti-abortion movement. I argue that these shifting problematisations reveal abortion regulation as a critical site of the biopolitical governance of gender, positioning women in deliberate and particular ways as befitting their proper gendered subjectivity—as mothers, nurturers, nation-builders, upholders of Christian morality. The corollary is women behaving badly, subverting their appropriate construction by seeking abortion. Thus, we meet women who are selfish, untrustworthy, murderous, unstable, victimised and vulnerable, but never a woman autonomous in her reproductive decision-making. On the eve of fundamental legislative and ideological reform, I question whether the proposed changes will really achieve a dissolution of the regime of reproductive control or whether they will merely reposition this control in a new site of gendered governance.